Ethnographic fieldwork using mobile technologies: case study of a Portuguese light festival - Garcia Ruiz, M. (2017)
This communication aims to share some of the results of the fieldwork undertaken during the Light Festivals that integrate Spectrum Network 2016. Spectrum program is based on a cooperation between five European countries - Croatia, Slovenia, Poland and Portugal - whose artists are called to present light artworks involving local communities in an educational and participatory perspective. Light Art Festivals have gain special relevance since they have been adopted by many City Councils to reactivate their municipalities, thru this ephemeral – or semipermanent- artistic implementation in public space. In addition, these events have opened an emerging new kind of cultural tourism, based on a very specialised public. This study is based on in-depth interviews with light-artist and light-festival curators, as well as a longitudinal audio-visual review of the events developed from 2008 to today by using netnografic methods. This ethnographic work tries to extend the age-old question of what is art (focusing on applied light art), what is its usefulness, its benefits for the municipalities -in which these types of festivals are deployed- and its perceived value. Furthermore, this work tries to question if light festivals are a simple trend or the events of light will last in time.